Efektivitas Aromaterapi Lavender dan Teknik Deep Breathing dalam Mengurangi Kecemasan Pada Ibu Hamil Menjelang Persalinan SC di RSU Nurhayati Garut Tahun 2025 - Kusnadi, Siti Farah Nisa; Mardiyah, Maryam Syarah; Hidayani, Hidayani (Innovative: Journal Of Social Science Research, 2025)
Anxiety is a common thing experienced by pregnant women approaching childbirth, especially Caesarean section (CS). One effort to reduce anxiety is to provide lavender aromatherapy and deep breathing techniques. This study aims to compare the effectiveness of lavender aromatherapy and deep breathing techniques on the anxiety of pregnant women before CS delivery at Nurhayati Garut Hospital in 2025. The study used a quasi-experimental design with a pre-test - post-test two group design approach. The study population was pregnant women in the third trimester approaching CS delivery, with a total sampling technique of 56 people. The results of the study showed that giving lavender aromatherapy and deep breathing techniques was effective in reducing anxiety. The results of the Wilcoxon and Mann-Whitney Test statistical tests obtained a p value = 0.043 (p <0.05) meaning that there was a difference in effectiveness between giving lavender aromatherapy and deep breathing techniques where deep breathing techniques more effective in reducing anxiety than lavender aromatherapy. Suggestions, hospitals can consider implementing deep breathing techniques as a relaxation method to reduce anxiety